Problem Behaviors as Perceived by Parents Before Their First Consultation at A Developmental Outpatient Clinic: A Questionnaire Research Study: Life Sciences -Psychiatry - Kuranami, Takaaki; Saito, Makoto; Gemba, Kiminori; Oda, Tetsuaki (International Journal of Life Science and Pharma Research, 2023)
Previous studies have suggested the importance of early detection of child developmental disorders and support forchildren and their parents. Child developmental and parental support are provided at both public and private facilities. Still,obtaining a physician’s diagnosis at a medical institution is essential to determine whether a person has a developmental disorder.However, diagnosing a developmental disorder at the first visit to a medical institution with a child development outpatient clinicis time-consuming. Furthermore, developmental disorders are often associated with multiple comorbidities. Parents must identifychildren’s problem behaviors before taking them to an outpatient clinic and understand how they consider such behaviors forappropriate diagnosis. Therefore, in this study, a private developmental support service company surveyed parents who had visiteda child development outpatient clinic at a medical institution. Chi-square test analysis revealed that the number of parents of boyshaving ≥2 problem behaviors was significantly higher than that of parents of girls (P< 0.01). In addition, parents who waited fortheir first medical visit for >0.5 years used multiple resources rather than a single resource to gain knowledge on their child’sproblem behaviors (P< 0.01). Therefore, parents of boys who visited the developmental outpatient clinic for the first time werealready aware of their children’s multiple problem behaviors before the examination; when the waiting period was prolonged, theparents used multiple resources to collect information before visiting a medical institution.